Detection of eight common β-globin gene mutation in thalassemia major patients using real time polymerase chain reaction (PCR)-high resolution melting and EvaGreen™ dye - Marash, Seyed Jalal; Eshkoor, Sima Ataollahi; Mirinargesi, Mir Saed; Sarookhani, Mohammad Reza; Rahmat, Asmah; Ismail, Patimah (Academic Journals, 2012)
The aim of the present study was to determine the phenotype and genotype frequency of the most common β-globin mutations among the thalassemia major (TM) patients, using high-resolution melting (HRM) curve analysis as a novel, reliable and rapid scanning method. In this descriptive-analytical study, real time polymerase chain reaction (PCR) was applied besides HRM assay in the same reaction tube for mutation detection by melting curve behavior analysis of EvaGreen™ dye. The phenotypic and genotypic frequency of β-globin mutations between 120 patients including IVS-II-1(G-A), IVS-I-110 (G-A), IVS-I-5(G-C), FSC 8/9, FSC 36/37, Codon 30, IVS-I-6 (T-C) and IVS-I-1(G-A) was successfully detected. TM patients showed significant genotype heterogeneity. The clinical outcomes of our TM patients were mostly explained by the genotypes linked to the β0 type of β- tahalssemia. Genotypic analysis showed 70 patients with homozygous mutations TM (40 β0/ β0 and 30 β+/ β+) and 15 with compound heterozygous TM (14 β+/ β0 and 1 β0/Hb Variant). HRM method as a simpler and cost effective way, accurately characterized the molecular basis of the TM patients.